Vibration Transmissibility on a System of Three Degrees of Freedom - Widodo, Widio
Rotating machinery is a commonly used tool in the industry. Those types of equipment often cause vibration during its operation process due to dynamic force. The vibration can be transmitted to the other machine located around and to the surrounding environment. Isolation vibration system is used to reduce the transmitted vibration so that further damage can be avoided. Knowing about vibration isolator that can pull off a small value of vibration transmissibility is essential in the preinstallation process. This can be achieved through modeling and testing on a simple system. This research is aimed to study the vibration transmissibility on a system of three degrees of freedom. The research begins with derivating the equation of vibration transmissibility and spring stiffness. The research is continued with identifying dynamic parameters, namely spring stiffness and damping constants. Spring stiffness is obtained by static testing while damping constants are obtained by testing on every mass-spring pair. These two parameters are used to make modeling graph. Then, vibration transmissibility testing is carried out using a shaker and unbalanced mass. The vibration transmissibility graph obtained is then compared and analyzed. In this research, the spring stiffness equation can be used to predict the spring stiffness needed so that the vibration transmissibility is conforming to criteria. Also, system modeling produces vibration transmissibility graph that is close to the transmissibility graph from testing.